Determinants of Stress and Coping Mechanisms Adopted among Medical Undergraduate Students in Coastal Karnataka, India: A Cross-Sectional Study - Pai, Divya Venkatesh; Sanjay Kini B; Kumar, Shishir; Muthukumar R; Vinu E; Sandesh Kini B; Singh, Manveer (National Journal of Community Medicine, 2023)
Background: The progressively worsening performance of students in classroom, the health problems induced due to stress, below average academic accomplishments of students in classroom and in hospital postings is directly attributable to the tremendous stress, medical students undergo during their course to become future doctors of the country. We conducted this research survey to find out the magnitude of stress as perceived by medical undergraduate students and to measure the association of such stress with various factors which may influence it. Methodology: About 612 students studying in private medical colleges in Mangalore from first year to final year were interviewed after obtaining their informed consent. The data collection tool used for this study consisted of a pre-designed questionnaire which contained social and demographic variables of study participants and a perceived stress scale developed by Cohen et al. Results: The immenseness of curriculum which was the academic stressor that was cited, financial and family issues were psychological stressors and accommodation which was the environmental stressor were some of the significant factors contributing towards perceived stress. Conclusion: Only one of the coping strategies adopted by students was found to be significantly associated with perceived stress.